The treatment of sinusitis following maxillary sinus grafting with the association of functional endoscopic sinus surgery (FESS) and an intra‐oral approach. Issue 6 (8th March 2012) - Chiapasco, M.; Felisati, G.; Zaniboni, M.; Pipolo, C.; Borloni, R.; Lozza, P.
Abstract Aim of the study To present the results of a prospective study on the management of infectious complications following maxillary sinus floor elevation procedures with a combined endoscopic (FESS) and intra‐oral approach. Materials and methods From 2005 to 2009, twenty consecutive patients were diagnosed for sinusal chronic infectious complications refractory to medical treatment following maxillary sinus floor elevation and grafting procedures. All patients were treated with a combination of functional endoscopic sinus surgery (FESS) through a transnasal approach and an intra‐oral approach, performed by an ear, nose, and throat team and an oral and maxillofacial team, respectively, in the same surgical session under general anesthesia. Results In 16 of 20 patients, the 4‐week endoscopic control demonstrated a complete clinical healing and recovery of the normal sinus ventilation and drainage. In two patients, the persisting sinusitis at the 4‐week control was successfully treated (8th week) with an antibiotic therapy based on the antibiogram carried out on the bacterial culture obtained by the aspiration of the sinusal content. In one patient, the persisting sinusitis (3 months after surgery) was successfully treated with the aspiration of the infectious material from the maxillary sinus. In one patient, finally, it was necessary to perform a second combined surgical treatment to treat the persisting sinusitis. Discussion and conclusions In this study, a relevant number of cases of chronic infectious complications following sinus floor elevation procedures are presented. To the authors' knowledge, it is the first time that well‐defined treatment protocols based on a combined endoscopic (FESS) and intra‐oral surgical approach are proposed. The positive, albeit preliminary, results obtained in this study seem to validate this treatment modality.